THE GRAPH OF DIAGRAM GROUPS FROM DIRECT PRODUCT OF THREE FREE SEMIGROUPS - Gemawati, Sri; Bin Ahmad, Abd. Ghafur (Journal of the Indonesian Mathematical Society, 2007)
"PDF File"DOI :Â http://dx.doi.org/10.22342/jims.13.2.68.209-214